A narrativa histórica de Tucídides e a Guerra do Peloponeso: verdade e ficção - Monteiro, Rafael Ferreira (2014)
The Greek historian Thucydides wrote his History of the Peloponnesian War because he realized that war would be big, the biggest one ever happened. His work marks a transition of narrative technique: if in Herodotus, the father of History, according to the Latin orator Cicero, the fable persists, in Thucydides there is a break with the mythos, that is, the narrative is constructed by concrete, researched and previously analyzed terms (logos). This removal is, however, seeming. In fact, the historian makes use of reason to make his narrative, as well as he sometimes uses a language “dry” and “rough” and he asserts to keep himself stick only to facts. Then how can we relate him to a literary world? We should analyze the picture of the historian from another perspective. Like asserts White (1994), the perspective of how an historical situation depends on the subtlety harmony between the structure of the plot and the group of actions that build, by way of this process, a literary operation, which creates the fiction. The author researches, gathers, analyzes, interprets and, finally, recreates the facts, rearranges and reconfigures them, in order to produce something concrete, impartial. However, the historical is not that simple: there are many possible interpretations, and there are many intersections with other genres (like epic, tragedy and comedy), and with other areas of knowledge (philosophy, politics, economy). Thus, the aim of this work is precisely to point out these characteristic of the text, proving the artistic value, the work with the Greek language and the constructive imagination of the Greek historian when he writes his work.